Isolation of Lactoferrin from raw and commercial milk samples followed by the observation of antimicrobial activity against Pathogens - Mimmi, Syeda Fahria Hoque (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.